(3efgLjI GdHMK GdYdej (B:s (3cja JcJH HMKG LGeYjG fGLMG aj GdYdhe GdGbJUGOjI? (B/s - (3RGjQj, HdbGSes ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3jMGhd gPG GdcJGH JbOje JUhQ Ydej hYedj Mhd cjajI GYOGO GdCHMGK GdYdejI hePcQGJ GdJNQL HGdfSHI dWdHI GdYdhe GdGbJUGOjI hJhLjg GdWdHI aj eSJhjGJ GdeGSJQ hGdOcJhQGg Edi GdefgLjI GdUMjMI hGdSdjeI dGfLGR GdCHMGK hGdePcQGJ hMJi GdebGdGJ GdYdejI PGJ GdfhYjI GdLjOI, hefg abO JfGhd aj aUhdg eGgjI GdHMK GdYdej heQGMdg heUGOQ GdHMK GdYdej CgejJgG hCfhGYgG hcja jJe cJGHJgG , hGdeYGjjQ GdNGUI HUjGZI GdHMK aj Tcdg GdfgGFj(B.s
(3GdeQGLY U(B.349s
Keywords: (3GdYdhe GdGLJeGYjIs; (3WQb GdHMKs; (3efGgL GdHMK GdYdejs